2005
DOI: 10.1093/brain/awh602
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of cognition in primary progressive multiple sclerosis

Abstract: There are few longitudinal studies of cognition in patients with multiple sclerosis, and the results of these studies remain inconclusive. No serial neuropsychological data of an exclusively primary progressive series are available. Cross-sectional analyses have revealed significant correlations between cognition and magnetic resonance imaging (MRI) parameters in primary progressive multiple sclerosis (PPMS). This study investigated cognitive and MRI change in 99 PPMS patients from five European centres for 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 54 publications
(84 reference statements)
9
77
1
2
Order By: Relevance
“…Previous longitudinal studies have highlighted the great interpatient variability in the cognitive outcome of patients with MS. However, a few well-designed longitudinal studies have consistently shown that nearly one third of patients deteriorate during 2-or 3-year follow-up periods 2,4,5,17 and the progression of cognitive dysfunction has been confirmed in a controlled 10-year observation. 3 In this study, we considered as deteriorating those patients who failed 1 or more tests compared with their baseline performance.…”
Section: Commentmentioning
confidence: 99%
“…Previous longitudinal studies have highlighted the great interpatient variability in the cognitive outcome of patients with MS. However, a few well-designed longitudinal studies have consistently shown that nearly one third of patients deteriorate during 2-or 3-year follow-up periods 2,4,5,17 and the progression of cognitive dysfunction has been confirmed in a controlled 10-year observation. 3 In this study, we considered as deteriorating those patients who failed 1 or more tests compared with their baseline performance.…”
Section: Commentmentioning
confidence: 99%
“…The insula has numerous connections with the cerebral cortex (frontal lobe, temporal lobe, parietal lobe and anterior cingulate cortex), the basal ganglia, the amygdala and other areas that are part of the limbic system, such as the parahippocampal cortex. As a consequence its involvement in PPMS patients might contribute to explain, at least in part, deficits of cognitive function often encountered in these patients [Camp et al, 2005].…”
Section: Assessment Of Volumetry and Diffusivity Changes In The Gmmentioning
confidence: 99%
“…A number of such studies have been published [8]. Their findings are highly inconsistent, with some studies documenting cognitive decline in at least a subset of the patients evaluated [9][10][11][12][13][14][15][16][17][18] and others offering little or no evidence of decline [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The most obvious distinction however is one of research design. The majority of these studies [12,13,17,21,23,24,[26][27][28] were uncontrolled and focused on the relationship between changes in patients' cognitive performance over time and brain imaging measures. Only six published reports of longitudinal studies [9][10][11][14][15][16] include a control group that was evaluated contemporaneously with the patient sample, and all of these studies provide evidence of cognitive deterioration in at least a subset of the patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation